Counterinsurgency in Pakistan - Jones, Seth G. (RAND Corporation, 2010)
Pakistan has undertaken a number of operations against militant groups since 2001. There have been some successes, but such groups as al Qa'ida continue to present a significant threat to Pakistan, the United States, and other countries. Pakistan needs to establish a population-centric counterinsurgency that better protects the local population and addresses grievances. It also needs to abandon militancy as a tool of foreign and domestic policy.